Sentosa : a lifestyle destination in the making? - Koh, Ming Ming. (2008)
This study aims to find out visitors’ experience and perceptions of the various plans of Sentosa. It also explores visitors’ future expectations of how Sentosa should develop, together with their awareness of the events and promotions in Sentosa and how appealing these programmes are to them.